The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/ppa.13032
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, molecular phylogenetic and pathogenic analyses of Erysiphe spp. causing powdery mildew on cashew plants in Brazil

Abstract: Cashew powdery mildew is presently the most important disease of cashew trees in all Brazilian growing regions. Although it was described over a century ago, it had never threatened the Brazilian cashew industry until the first decade of the 21st century. Morphological and pathogenic evidence indicated the possibility of different pathogen species being involved in early and late types of cashew powdery mildew. This study was designed to elucidate this issue by comparing two different powdery mildew fungi occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Erysiphe appeared as the second most frequently reported fungal genus, with two species recently reported in cashew in Brazil: E. quercicola [40][41][42] and E. necator [42]. Cashew powdery mildew (CPM) has been considered a minor disease that affects young leaves, inflorescences, and nuts, reducing fruit onset and severely damaging apple and kernels [40].…”
Section: Powdery Mildewmentioning
confidence: 99%
“…Erysiphe appeared as the second most frequently reported fungal genus, with two species recently reported in cashew in Brazil: E. quercicola [40][41][42] and E. necator [42]. Cashew powdery mildew (CPM) has been considered a minor disease that affects young leaves, inflorescences, and nuts, reducing fruit onset and severely damaging apple and kernels [40].…”
Section: Powdery Mildewmentioning
confidence: 99%
“…quercicola causing powdery mildew in cashew trees in Brazil (Cardoso et al, 2017), although it has already been reported as the cause of epidemics verified in Tanzania (Limkaisang et al, 2006). In another later study carried out by Fonseca, Cardoso, Ootani, Brasil, et al (2019) based on morphological, phylogenetic and pathogenic analyses, it was shown that two species are associated with cashew powdery mildew: E. quercicola , which infects young immature tissues such as young leaves, flowers and young fruits, and E. necator , which infects mature and shaded leaf tissues. This same study reported the first occurrence of both E .…”
Section: Introductionmentioning
confidence: 98%